2009
DOI: 10.1111/j.1440-1819.2008.01918.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased soluble tumor necrosis factor‐α receptors in patients with major depressive disorder

Abstract: Aim: Several lines of evidence suggest that major depressive disorder is associated with an inflammatory status. Tumor necrosis factor-a has been investigated as a potential molecular target in mood disorders. Tumor necrosis factor-a exerts its activity through binding to specific cell membrane receptors named as TNFR1 and TNFR2. The aim of the present study was to investigate soluble plasma TNFR1 (sTNFR1) and TNFR2 levels (sTNFR2) in major depressive disorder patients.Methods: Female outpatients with major de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 39 publications
5
53
2
1
Order By: Relevance
“…There is growing evidence supporting the link between traumatic stress to a pro-inflammatory profile [5] , with increasing serum concentrations of TNF-␣ , IFN-␥ , IL-1 ␤ and IL-6. Recently, we observed that depressed patients with or without PTSD symptoms had higher soluble TNF receptor 2 levels in contrast to lower IL-2 and chemokine RANTES levels compared to healthy controls [6] . The low-grade inflammatory response has been linked to disease severity.…”
Section: Low-grade Inflammationmentioning
confidence: 91%
“…There is growing evidence supporting the link between traumatic stress to a pro-inflammatory profile [5] , with increasing serum concentrations of TNF-␣ , IFN-␥ , IL-1 ␤ and IL-6. Recently, we observed that depressed patients with or without PTSD symptoms had higher soluble TNF receptor 2 levels in contrast to lower IL-2 and chemokine RANTES levels compared to healthy controls [6] . The low-grade inflammatory response has been linked to disease severity.…”
Section: Low-grade Inflammationmentioning
confidence: 91%
“…Of important note, the reduced IL-2 production could be interpreted as the underlying mechanism for blunted T cell responses. Major depression and PTSD have been associated with higher plasma levels of proinflammatory mediators such as acute phase proteins and cytokines [13][14][15][16] . However, little is known about secreted cytokine profiles in depression and discrepancies could be explained by methodological differences (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MDD has also been linked to reduced glucocorticoid-induced immunoregulation [11,12] and to low-grade inflammatory responses. Indeed, MDD has been related with higher levels of soluble tumor necrosis factor (TNF)-␣ receptors (sTNFR1 and sTNFR2) [13] as well as elevated proinflammatory cytokines and chemokines such as MCP-1, interleukin (IL)-1 ␤ , IL-6, IL-8, interferon (IFN)-␥ and TNF-␣ [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…This is especially more pronounced in patients with coexisting comorbidities such as congestive heart failure. Higher levels are also noticed in patients with depression secondary to "posttraumatic stress disorder" (3). A significant association is also seen between the age of the patients with major depression and the corresponding sTNFr1 levels.…”
mentioning
confidence: 87%